NAVIGATING THE COMPLEX SYNTHESIS OF ENVIRONMENTAL LAWS IN INDIA IN THE CONTEXT OF DETERIORATING FOREST COVER IN INDIA (Lex localis - Journal of Local Self-Government, 2025)
The article is a route on the labyrinth Indian attempting to integrate its environmental laws in the ambiguous environment the diminishing forest cover. India is a country of severe paradox that has one of the most sophisticated systems of environmental regulations yet has severe issues as far as its implementation is concerned, as revealed by the steadily declining deforestation, land degradation, and massive disparities in statistics. The main conflict that is going to be examined in the paper is the developmental goals of India and its conservationist requirements (Kandpal, 2024). It questions even the notion of a forest, a statistical and legal loophole that allows the sources of authority to report an increase in the forest cover (DD News, 2024) when the losses are so shocking that they attract the attention of critical commentators and the courts of law (Live Law, 2024; Kohli, 2025). The paper takes the chronology of the maturation of the main forest law in India the Forest (Conservation) Act, 1980, and the radical, protective judicial action in 1996 in the case Godavarman. Thereafter, it critically dissects the new Forest (Conservation) Amendment Act, 2023, stating that this is an axe-swung law upon its forests (The India Forum, 2024). The conclusion of the analysis is that the interface between science and policy is not harmonized because it is organized around conflicting knowledge systems (Bisht, 2022) that mislead on the reality of ecological degradation. Lastly, the paper recommends that the paradigm shift in the environmental governance paradigm should be founded on abandonment of a maladapted synthesis of statutes and laws environmentally in favor of an environmentally just, equitable (Tanwar and Poply, 2024), and sustainable community livelihoods management (Das and Mallick, 2024; Singh and Kaunert, 2025).